(untitled) (Lapai Journal of Economics, 2023)
This study focuses on the assessment of the Community and Social Development Projects (CSDP) on social infrastructure development in the Kwali Area Council of the Federal Capital Territory (FCT). Social infrastructure plays a vital role in enhancing the quality of life and well-being of a community’s residents. The research aims to evaluate the effectiveness and sustainability of the CSDP’s initiatives in promoting social infrastructural development within the Kwali Area Council. The study adopted the documentary research method through the review of various documents—books, journals, government publications, and other written materials that are relevant and valid in the area of study by subjecting the various information to deductive reasoning to find answers to research questions. The findings from the presented data highlighted the substantial impact of the Federal Capital Territory Community and Social Development Project (FCT-CSDP) on the development of social infrastructure in Kwali Area Council. The construction and rehabilitation initiatives undertaken through FCT-CSDP grants have significantly contributed to various aspects of the community. The study recommends that to ensure the continued benefits of the FCT-CSDP initiatives, it’s crucial to incorporate sustainability measures into project planning. This could involve training community members in the maintenance and management of the constructed facilities, creating income-generating activities linked to the projects, and establishing mechanisms for ongoing monitoring and evaluation.